(untitled) (The Insight, 2023)
Introduction: Stroke is a complex pathological condition that results in brain impairment across many age groups. In the past, stroke was predominantly considered a condition affecting older individuals but now it has revealed the occurrence of several stroke subtypes among young adults. Objective: The aim of this study was to determine the prevalence of stroke among the young adults and its risk factors. Method: This case-control study was conducted at the department of Neurology during January, 2021 to December, 2021 in Cox Bazar Medical College Hospital, Chattrogram, Bangladesh. Results: The mean age of the case group (n=58) was 23.31±2.01 years and 77.58% were male, 22.41% were female while in the control group (n=42), the mean age was 23.02±2.27 years and 50% were male and 50% were female. In the case group, .87.93% patients smoked, 93.10% had hypertension, 94.82% had diabetes, 13.79% had vasculitis, 20.68% had SLE, and 27.58% had cardiac arrhythmia while in the control group, 50% patients smoked, 69.04% had hypertension, 54.76% had diabetes, 2.38% had vasculitis, 4.76% had SLE, and 0% had cardiac arrhythmia(p<0.05)%)except vasculitis. The case group had 93.10% grey-white matter distinction and 87.93% CT hypodensity while no alteration was observed in the control group’s brain CT images(p=0.000). Conclusion: This study investigated that hemiplegia, slurring speech, blurring of vision, and headache are the major clinical presentations of the stroke in the young adults and smoking, hypertension, diabetes, SLE, and cardiac arrhythmia are the significant risk factors of occurring stroke in the young adults.